An Investigation of Organizational Presenteeism Among Teachers (Journal of Management and Educational Sciences, 2025)
The purpose of this study is to determine the levels of organizational presenteeism (not being present at work) perceived by teachers and to examine whether these levels differ according to demographic variables. Conducted using quantitative research methods, this study was carried out with data obtained from a total of 174 teachers working in the central district of Adıyaman. Data collection involved the use of a personal information form and the Organizational Presenteeism Scale developed by Uslukaya, Demirtaş, and Alanoğlu (2022), which consists of three sub-dimensions. Data analysis included normality tests, independent samples t-test, ANOVA, and Pearson correlation analysis. The results of the study revealed that teachers' overall presenteeism levels were moderate, with environmental factors being perceived as higher than individual and organizational factors. No significant differences were found in presenteeism levels according to gender, marital status, and educational status variables; however, some significant differences were found in certain sub-dimensions according to age and professional experience variables. In particular, it was determined that teachers aged 31–40 and with 11–15 years of experience had higher presenteeism perceptions. Correlation analyses revealed significant positive relationships between the sub-dimensions. The research findings indicate that teachers' behavior of coming to work even when sick is shaped by various individual, organizational, and environmental factors in educational institutions. In this context, it was concluded that policies prioritizing teacher health should be established and workplace culture should be restructured in this direction.